A novel hafnium-based ferroelectric memory and a method of manufacturing the same
Patent Information
- Application Number
- CN202310802656.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0003]但是铪基铁电的耐久性相比PZT较差,随着铪基铁电薄膜尺寸的不断微缩,多次重复读写过程会使得器件出现不可避免的耐久性问题
本申请利用与铁电层相同并具备铁电性的材料作为中间层,在抑制泄漏电流的同时能简化工艺,并为维持铁电存储器的极化强度。而采用不同的原子层沉积循环比率,使得中间层在抑制泄漏电流的同时,维持铁电存储器中铁电层的厚度,进一步兼顾了铁电存储器的极化强度和抑制泄漏电流。
Smart Images

Figure CN116744691B_ABST
Abstract
Description
Technical Field
[0001] This document relates to the field of memory technology, and in particular to a novel hafnium-based ferroelectric memory and its fabrication method. Background Technology
[0002] Ferroelectric memories, as a novel type of high-speed, low-power memory, possess great development potential. The two polarization states of ferroelectric materials enable the writing of data "0" and "1" under an applied voltage, and the retention of data even when power is off, making ferroelectric memories one of their important applications. The emergence of novel hafnium-based ferroelectrics can largely meet the requirements for size miniaturization and compatibility with CMOS processes, which are currently difficult to achieve with PZT.
[0003] However, hafnium-based ferroelectrics have poorer durability compared to PZT. As the size of hafnium-based ferroelectric thin films continues to shrink, repeated read and write processes will inevitably lead to durability issues in the devices. Summary of the Invention
[0004] Based on the above analysis, this application aims to propose a novel hafnium-based ferroelectric memory and its preparation method to improve the durability of hafnium-based ferroelectric memory.
[0005] In a first aspect, one or more embodiments of this specification provide a novel hafnium-based ferroelectric memory, characterized in that it comprises: Top electrode, bottom electrode, two ferroelectric layers and one intermediate layer; The intermediate layer is disposed between the two ferroelectric layers; the atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layer, and the material of the intermediate layer is the same as that of the ferroelectric layer and has ferroelectric properties; The two ferroelectric layers and the intermediate layer are disposed between the top electrode and the bottom electrode.
[0006] Furthermore, both ferroelectric layers and the intermediate layer are HZO ferroelectric layers.
[0007] Furthermore, the atomic layer deposition cycle ratio of the intermediate layer is: ZrO2 / HfO2 = 5 / 5; The atomic layer deposition cycle ratio of the two ferroelectric layers is: ZrO2 / HfO2=1 / 1.
[0008] Furthermore, the thickness of the intermediate layer is 1-2 nm; The thickness of the ferroelectric layer is 4-5 nm.
[0009] Secondly, embodiments of this application provide a method for fabricating the novel hafnium-based ferroelectric memory as described in any of the first aspects, comprising: On the bottom electrode, based on atomic layer deposition, the precursor for growing HfO2 is Hf[N(C2H5)CH3]4, and the precursor for growing ZrO2 is Zr[N(C2H5)CH3]4, thus obtaining a ferroelectric layer-intermediate layer-ferroelectric layer in sequence. The atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layer, and the material of the intermediate layer is the same as that of the ferroelectric layer.
[0010] The process of sequentially obtaining a ferroelectric layer-intermediate layer-ferroelectric layer includes: On the bottom electrode, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer. On the obtained ferroelectric layer, the intermediate layer is obtained by alternating deposition of 5-cycle ZrO2 layers and 5-cycle HfO2 layers. On the obtained intermediate layer, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer.
[0011] Further, the ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer, comprising: One cycle of ZrO2 and one cycle of HfO2 constitute one large cycle, and a total of 20-25 large cycles are deposited.
[0012] Furthermore, the process involves depositing one cycle of ZrO2 and one cycle of HfO2 as a single large cycle, for a total of 20-25 large cycles, including: According to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing one layer of ZrO2, then another layer, and then another layer of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
[0013] Further, the intermediate layer is obtained by alternating deposition of 5 cycles of ZrO2 layers and 5 cycles of HfO2 layers, comprising: A large cycle consists of 5 cycles of ZrO2 and 5 cycles of HfO2, and a total of 1-2 large cycles are deposited.
[0014] Furthermore, according to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing 5 layers of ZrO2, then preparing one layer, and then preparing 5 layers of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
[0015] Compared with the prior art, this application can achieve at least the following technical effects: This application utilizes a material identical to and possessing ferroelectric properties as the intermediate layer. This simplifies the process while suppressing leakage current and maintaining the polarization intensity of the ferroelectric memory. By employing different atomic layer deposition cycle ratios, the intermediate layer can suppress leakage current while maintaining the thickness of the ferroelectric layer in the ferroelectric memory, further balancing the polarization intensity and leakage current suppression of the ferroelectric memory. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in one or more embodiments of this specification or in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this specification. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 A schematic diagram of the structure of a novel hafnium-based ferroelectric memory provided for one or more embodiments of this specification; Figure 2 A schematic diagram of the existing device provided as an example in this specification; Figure 3 Hysteresis loops of the HZO1 / 1 and HZO1 / 5 / 1 devices provided in this specification; Figure 4 The initial state JV curves of the HZO1 / 1 and HZO1 / 5 / 1 devices provided as examples in this specification; Figure 5 The leakage current of the HZO1 / 1 and HZO1 / 5 / 1 devices provided in this specification varies with the number of field cycles. Figure 6 The residual polarization intensity of the HZO1 / 1 and HZO1 / 5 / 1 devices provided as examples in this specification varies with the number of field cycles. Detailed Implementation
[0018] To enable those skilled in the art to better understand the technical solutions in one or more embodiments of this specification, the technical solutions in one or more embodiments of this specification will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this specification, and not all of the embodiments. Based on one or more embodiments of this specification, all other embodiments obtained by those skilled in the art without creative effort should fall within the protection scope of this document.
[0019] For existing ferroelectric memories, with increasing read / write cycles, defects, especially oxygen vacancies, lead to two main problems: firstly, increased leakage current in the ferroelectric thin film, potentially causing irreversible hard breakdown; and secondly, a decrease in remanent polarization, resulting in a reduced storage window and degraded performance. Furthermore, existing insertion layers are typically AlO₂. x Materials such as these can improve the durability of HZO films, but they also significantly affect the remanent polarization of the films, leading to a reduction in the storage window.
[0020] To address the aforementioned technical problems, this application provides a novel hafnium-based ferroelectric memory. Figure 1 As shown, it includes: The structure consists of a top electrode, a bottom electrode, two ferroelectric layers, and an intermediate layer. The intermediate layer is positioned between the two ferroelectric layers. The atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layers, and the intermediate layer is made of the same material as the ferroelectric layers and possesses ferroelectric properties. The two ferroelectric layers and the intermediate layer are positioned between the top electrode and the bottom electrode.
[0021] If the intermediate layer and the two ferroelectric layers are made of different materials, it means that at least two processes are required to fabricate the ferroelectric memory. Furthermore, different materials at the grain boundaries that disrupt the continuous growth of the ferroelectric layer film not only suppress leakage current but also reduce the residual polarization intensity of the ferroelectric layer. Therefore, in this embodiment, both the two ferroelectric layers and the intermediate layer are HZO ferroelectric layers.
[0022] In this embodiment, both the ferroelectric layer and the intermediate layer are composed of multiple repeating units, and each repeating unit contains the same number of ZrO2 layers and HfO2 layers. The ZrO2 and HfO2 layers are characterized by the atomic layer deposition cycle ratio. For example, for the intermediate layer, the atomic layer deposition cycle ratio is ZrO2 / HfO2 = 5 / 5, so there are 5 ZrO2 layers and 5 HfO2 layers in one repeating unit. For the ferroelectric layer, the atomic layer deposition cycle ratio is ZrO2 / HfO2 = 1 / 1, so there is 1 ZrO2 layer and 1 HfO2 layer in one repeating unit.
[0023] During field cycling, in HZO1 / 1, oxygen vacancies tend to form conductive paths between the top and bottom electrodes. In HZO1 / 5 / 1, because oxygen vacancies are less likely to accumulate in the thicker ZrO2 layer and are distributed in a dispersed manner, multiple cycles of stacking can block the development of leakage current conduction paths, thereby improving the durability and reliability of the device. Therefore, this application achieves leakage current suppression using the same material by changing the atomic layer deposition cycle ratio.
[0024] In the prior art, the ferroelectric layer of ferroelectric memory is 10-12 nm thick, while in this application, the thickness of the intermediate layer is 1-2 nm and the thickness of the ferroelectric layer is 4-5 nm. Therefore, although this application adds an intermediate layer, the overall thickness of the ferroelectric layer does not increase. Increasing the thickness of the ferroelectric layer would lead to a decrease in the polarization intensity of the ferroelectric memory. Therefore, the technical solution of this application can simultaneously suppress leakage current and maintain the performance of the ferroelectric memory.
[0025] This application provides a method for fabricating the memory described in any of the foregoing embodiments: On the bottom electrode, based on atomic layer deposition, the precursor for growing HfO2 is Hf[N(C2H5)CH3]4, and the precursor for growing ZrO2 is Zr[N(C2H5)CH3]4, thus obtaining a ferroelectric layer-intermediate layer-ferroelectric layer in sequence. The atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layer, and the material of the intermediate layer is the same as that of the ferroelectric layer.
[0026] Specifically, the fabrication method of the ferroelectric layer-intermediate layer-ferroelectric layer structure is as follows: On the bottom electrode, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer.
[0027] In the embodiments of this application, a repeating unit of the ferroelectric layer contains a ZrO2 layer and an HfO2 layer, each layer being 1 Å. Each ZrO2 layer is referred to as a 1-cycle ZrO2 layer, and each HfO2 layer is referred to as a 1-cycle HfO2 layer.
[0028] An intermediate layer was obtained by alternating deposition of 5-cycle ZrO2 layers and 5-cycle HfO2 layers on the obtained ferroelectric layer.
[0029] In the embodiments of this application, a repeating unit in the intermediate layer contains 5 ZrO2 layers and 5 HfO2 layers, each layer being 1 Å. Each ZrO2 layer is referred to as a 5-cycle ZrO2 layer, and each HfO2 layer is referred to as a 5-cycle HfO2 layer.
[0030] On the obtained intermediate layer, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer.
[0031] In this embodiment of the application, for the ferroelectric layer, the alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer is specifically: one cycle of ZrO2 and one cycle of HfO2 constitute one large cycle, and a total of 20-25 large cycles are deposited.
[0032] In this embodiment of the application, for the intermediate layer, the alternating deposition of 5-cycle ZrO2 layers and 5-cycle HfO2 layers specifically means that 5-cycle ZrO2 and 5-cycle HfO2 constitute one large cycle, and a total of 1-2 large cycles are deposited.
[0033] It should be noted that the above alternation process can all be implemented based on software and programs: Specifically, for the ferroelectric layer, According to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing one layer of ZrO2, then another layer, and then another layer of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
[0034] For the intermediate layer According to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing 5 layers of ZrO2, then preparing one layer, and then preparing 5 layers of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
[0035] To illustrate the feasibility and technical effectiveness of the above method, this application provides Example 1 (control group) and Example 2 (experimental group).
[0036] Example 1 Step 1: Using a Si substrate with a SiO2 thickness of 300 nm, a 40 nm thick TiN bottom electrode is prepared by ion beam sputtering to serve as a conductive electrode.
[0037] Step 2: On the TiN bottom electrode, a ferroelectric layer is prepared using atomic layer deposition (ALD) at a deposition temperature of 280℃. The precursor for HfO2 growth is Hf[N(C2H5)CH3]4 (TDMAHf), and the precursor for ZrO2 growth is Zr[N(C2H5)CH3]4 (TDMAZr), with H2O as the oxygen source. The HZO thin film growth begins with a ZrO2 layer. A 12nm thick HZO1 / 1 ferroelectric layer is grown. One cycle of ZrO2 (1Å) and one cycle of HfO2 (1Å) are deposited alternately, with ZrO2 / HfO2 = 1 / 1. One cycle of ZrO2 and one cycle of HfO2 constitutes one large cycle, and a total of 60 large cycles are deposited.
[0038] Step 3: Photolithography, top electrode patterning.
[0039] Step 4: A 40 nm thick TiN top electrode is fabricated on a 12 nm HZO ferroelectric layer using ion beam sputtering.
[0040] Step 5: Peeling.
[0041] Step 6: The device is annealed using Rapid Thermal Annealing (RTA) at a temperature of 500℃ for 30 seconds under an N2 atmosphere.
[0042] The structure obtained in Example 1 is as follows Figure 2 As shown.
[0043] Example 2 Step 1: Using a Si substrate with a SiO2 thickness of 300 nm, a 40 nm thick TiN bottom electrode is prepared by ion beam sputtering to serve as a conductive electrode.
[0044] Step 2: A ferroelectric layer was prepared on the TiN bottom electrode using atomic layer deposition (ALD) at a deposition temperature of 280℃. The precursor for HfO2 growth was Hf[N(C2H5)CH3]4 (TDMAHf), and the precursor for ZrO2 growth was Zr[N(C2H5)CH3]4 (TDMAZr). H2O was used as the oxygen source. The HZO thin film growth started with the ZrO2 layer.
[0045] (1) Grow a 5 nm thick HZO1 / 1 ferroelectric layer. Alternately deposit 1 cycle of ZrO2 layer (1 Å) and 1 cycle of HfO2 layer (1 Å), ZrO2 / HfO2=1 / 1, with 1 cycle of ZrO2 and 1 cycle of HfO2 as one large cycle, for a total of 25 large cycles. (2) Grow a 2 nm thick HZO5 / 5 ferroelectric intermediate layer. Change the ALD deposition cycle ratio, and alternately deposit the intermediate layer with 5 cycles of ZrO2 layer (5 Å) and 5 cycles of HfO2 layer (5 Å), ZrO2 / HfO2=5 / 5, for 2 large cycles. (3) Repeat the initial deposition method to grow a 5 nm thick HZO1 / 1 ferroelectric layer.
[0046] Step 3: Photolithography, top electrode patterning.
[0047] Step 4: A 50 nm thick TiN top electrode is fabricated on a 12 nm HZO ferroelectric layer using ion beam sputtering.
[0048] Step 5: Peeling.
[0049] Step 6: The device is annealed using Rapid Thermal Annealing (RTA) at a temperature of 500℃ for 30 seconds under an N2 atmosphere.
[0050] In the embodiments of this application, such as Figure 3As shown, the residual polarization intensity of the device (HZO1 / 5 / 1) provided in this application is similar to that of the existing device (HZO1 / 1), indicating that the device does not damage the polarization value of the existing device.
[0051] In the embodiments of this application, such as Figure 4 As shown, under the same scanning voltage test conditions, the device (HZO1 / 5 / 1) provided in this application exhibits a reduced initial-state current density. At a voltage of 1V, the current density of the device is reduced by an order of magnitude compared to existing devices, reaching 2.18 × 10⁻⁶. -8 A / cm 2 (HZO1 / 1) decreased to 1.51×10 -9 A / cm 2 (HZO1 / 5 / 1). This indicates that when multiple-cycle stacks are used as intermediate layers, leakage current can be effectively suppressed.
[0052] In the embodiments of this application, such as Figure 5 and Figure 6 As shown, the leakage current reading voltage is 3V. During the gradual increase of the field cycle number, the existing device... 6 Hard breakdown subsequently occurs. The device provided in this application has a field cycle count up to 10. 8 No hard breakdown occurred, and durability was improved by more than two orders of magnitude. At 10 8 Under the given number of field cycles, the leakage current of the device provided in this application does not show a sharp increase, and the growth trend is relatively gradual. Furthermore, the device still maintains a sufficient storage window in terms of remanent polarization intensity. This indicates that this patent can effectively improve the durability characteristics of HZO ferroelectric devices while maintaining a sufficient storage window.
[0053] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0054] One or more embodiments of this specification can be described in the general context of computer-executable instructions, such as program modules, that are executed by a computer. Generally, program modules include routines, programs, objects, components, data structures, etc., that perform a particular task or implement a particular abstract data type. One or more embodiments of this specification can also be practiced in distributed computing environments where tasks are performed by remote processing devices connected via a communication network. In distributed computing environments, program modules can reside in local and remote computer storage media, including storage devices.
[0055] The various embodiments in this specification are described in a progressive manner. Similar or identical parts between embodiments can be referred to interchangeably. Each embodiment focuses on describing the differences from other embodiments. In particular, the system embodiments are basically similar to the method embodiments, so the description is relatively simple; relevant parts can be referred to the descriptions in the method embodiments.
[0056] The above description is merely an embodiment of this document and is not intended to limit the scope of this document. Various modifications and variations can be made to this document by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this document should be included within the scope of the claims of this document.
Claims
1. A novel hafnium-based ferroelectric memory, characterized in that, include: Top electrode, bottom electrode, two ferroelectric layers and one intermediate layer; The intermediate layer is disposed between the two ferroelectric layers; The atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layer, and the material of the intermediate layer is the same as that of the ferroelectric layer and has ferroelectric properties; The two ferroelectric layers and the intermediate layer are disposed between the top electrode and the bottom electrode; The atomic layer deposition cycle ratio of the intermediate layer is: ZrO2 / HfO2=5 / 5; The atomic layer deposition cycle ratio of the two ferroelectric layers is: ZrO2 / HfO2=1 / 1.
2. The memory according to claim 1, characterized in that, The two ferroelectric layers and the intermediate layer are all HZO ferroelectric layers.
3. The memory according to claim 1, characterized in that, The thickness of the intermediate layer is 1-2 nm; The thickness of the ferroelectric layer is 4-5 nm.
4. A method for preparing a novel hafnium-based ferroelectric memory according to any one of claims 1-3, characterized in that, include: On the bottom electrode, based on atomic layer deposition, the precursor for growing HfO2 is Hf[N(C2H5)CH3]4, and the precursor for growing ZrO2 is Zr[N(C2H5)CH3]4, thus obtaining a ferroelectric layer-intermediate layer-ferroelectric layer in sequence. The atomic layer deposition cycle ratio of the intermediate layer is different from that of the ferroelectric layer, and the material of the intermediate layer is the same as that of the ferroelectric layer.
5. The method according to claim 4, characterized in that, The process of sequentially obtaining a ferroelectric layer-intermediate layer-ferroelectric layer includes: On the bottom electrode, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer. On the obtained ferroelectric layer, the intermediate layer is obtained by alternating deposition of 5-cycle ZrO2 layers and 5-cycle HfO2 layers. On the obtained intermediate layer, a ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer.
6. The method according to claim 5, characterized in that, The ferroelectric layer is obtained by alternating deposition of one cycle of ZrO2 layer and one cycle of HfO2 layer, including: One cycle of ZrO2 and one cycle of HfO2 constitute one large cycle, and a total of 20-25 large cycles are deposited.
7. The method according to claim 6, characterized in that, The process involves depositing 20-25 large cycles, consisting of one cycle of ZrO2 and one cycle of HfO2, totaling 1 large cycle. According to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing one layer of ZrO2, then another layer, and then another layer of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
8. The method according to claim 5, characterized in that, The intermediate layer is obtained by alternating deposition of 5 cycles of ZrO2 layers and 5 cycles of HfO2 layers, comprising: A large cycle consists of 5 cycles of ZrO2 and 5 cycles of HfO2, and a total of 1-2 large cycles are deposited.
9. The method according to claim 8, characterized in that, According to the preset atomic layer deposition cycle ratio, a large cycle is completed by first preparing 5 layers of ZrO2 and then preparing 5 layers of HfO2. Record the number of completed loops; Repeat the above steps until the number of completed large loops reaches the preset number.
Citation Information
Patent Citations
Ferroelectric capacitor, transistor, memory device, and method of manufacturing ferroelectric device
CN113130749A
Method for preparing HZO ferroelectric film at low temperature and HZO ferroelectric film
CN114990530A